E-Banking: The Indian Scenario: A Comprehensive Analysis of E-Banking in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
E-banking is the new age banking. Gone are the days when banking was confined to only brick and mortar. The prodigious advancement in technology had brought a colossal shift in banking operations. You are no longer required to visit bank, banking is at your doorstep, on your table or even in your pocket accessible 24X7. Plastic money is handier than paper money. Banking itself has come a long way from ‘nice to have to need to have’. Banks today are highly globalised, liberalized and privatized. Banking sector is the backbone of the country’s economic growth, and yes India is no exception to it. Indian banking sector is observing an IT revolution. Indian banks needs to pursue a world class internet banking capability. Banking today has shifted from product centric to customer centric. This E-banking approach has benefited both: customers and banks. The Reserve Bank of India in its vision 2018 statement has set the objective to actively promote electronic payments aiming towards ‘less cash’ society. The intent of this paper is to analyze the ongoing scenario of E-banking and its different channels and studying various challenges and its future. The study is secondary based and analytical in nature.